Does community pressure matter in cesarean deliveries in Bangladesh? An analysis of nationally representative surveys - Md Rabiul Haque; Ahbab Mohammad Fazle Rabbi; Mohammad Sazzad Hasan; Fardin Araf; Md Saidul Islam (PLoS ONE, 2025)
Cesarean delivery plays a significant role in reducing maternal and child mortality. However, unjustified cesarean section (C-section) delivery is rising worldwide, including in Bangladesh. C-section delivery rates in Bangladesh have increased from 2.9% in 1999 to 45% in 2022, which is particularly high for first-order births (51%). This study aims to describe the prevalence and determinants of births by C-section for institutional deliveries in Bangladesh’s private and public health facilities. Data from the Bangladesh Demographic and Health Surveys (BDHS) for 2011, 2014, 2017−18, and 2022 are used in this study. Besides the common socio-economic determinants of C-sections, adequate antenatal care (ANC) visits, place of delivery (public/private), and community-level factors including level of illiteracy and prevalence of C-sections in the community were found to have a significant association. After controlling the effect of other variables, women from a community with a high prevalence of C-sections were found to be 11.68 times more likely to have a C-section in their last birth compared to women from a community with a low prevalence of C-sections. Also, the women who had their last birth in private facilities were 8.16 times more likely to have C-sections than women who delivered in public facilities. These findings suggest that the increased rate of C-sections in Bangladesh may be driven by both individual-level and provider-level factors where community pressure plays a vital role. Close monitoring, particularly in private hospitals, and community-level awareness programs about the adversity of C-sections are the proposed policy strategies to avoid unnecessary cesarean deliveries in Bangladesh.